Interdisciplinary maxillary orthopaedic treatment of a patient with perinatal trauma - Gabrielli, Carolina Guadalupe (2018)
Fil: Gabrielli, Carolina Guadalupe. Universidad Nacional de Córdoba. Facultad de Odontología; Argentina.